Differential Cross Section and Polarization of Radiative Recombination - 吴泽清 李月明 段斌 张弘 颜君 (Chinese physics letters, 2009)
The formulae of photon angular distribution and polarization degree for radiative recombination are presented to include the contribution of multipoles and their correlations. A fully relativistic code is then developed to calculate the photon angular distribution and polarization. The calculated polarization degree and differential cross-sections agree well with that of Scofild＇s results within 10%. The effects of multipoles on polarization and angular distribution are investigated. The polarization and the angular distribution become asymmetric when the multipoles are accounted as the electron energy increases.